A comparison of two stretching programs for hamstring muscles: A randomized controlled assessor-blinded study. (2nd January 2016) - Demoulin, Christophe; Wolfs, Sébastien; Chevalier, Madeline; Granado, Caroline; Grosdent, Stéphanie; Depas, Yannick; Roussel, Nathalie; Hage, Renaud; Vanderthommen, Marc
ABSTRACT: Most parameters regarding hamstring flexibility training programs have been investigated; however, the joint (i.e. hip or knee) on which the stretching should preferentially be focused needs to be further explored. This randomized controlled assessor-blinded study aimed to investigate the influence of this parameter. We randomly assigned 111 asymptomatic participants with tight hamstring muscles in three groups: a control group and two groups following a different home-based 8-week (five 10-minute sessions per week) hamstring stretching program (i.e. stretching performed by flexing the hip while keeping the knee extended [SH] or by first flexing the hip with a flexed knee and then extending the knee [SK]). Range of motion (ROM) of hip flexion and knee extension were measured before and after the stretching program by means of the straight leg raising test and the passive knee extension angle test, respectively. Eighty-nine participants completed the study. A significant increase in ROM was observed at post-test. Analyses showed significant group-by-time interactions for changes regarding all outcomes. Whereas the increase in hip flexion and knee extension ROM was higher in the stretching groups than in the CG (especially for the SH group p < 0.05), no differences between the two stretching groups were observed ( p > 0.05). In conclusion, the fact that both stretching programs resulted in similar results suggests no influence of the joint at which the stretching is focused upon, as assessed by the straight leg raising and knee extension angle tests.